Relationship between confucian heritage culture and preference to active learning among Chinese pre-university Students / Choong Shiau Huai - Choong , Shiau Huai (2019)
Educational borrowing of active learning into Asian countries, especially countries with a Confucian Heritage Culture (CHC) background, appears to have caused dilemmas which emerged from cross-cultural differences among teachers and students. Some students with CHC background are reported to resist active learning (AL). The present study aimed to conceptually define these two constructs and develop two scales, namely the Confucian Heritage Culture (CHC) Scale and the Preference to Active Learning (PtAL) Scale, which were used to predict the relationship between Confucian Heritage Culture and learning preference to active learning, by adopting philosophical, psychological, political science, and educational perspectives. In accordance with the research objectives, a correlational research design was adopted in the study. The study was conducted in two phases. In Phase 1, the scales were developed and validated, and these instruments were pre-tested. Then in Phase 2, the model put forward was validated, relationship was explored and theory was developed. Data for scale development was collected from 430 Chinese pre-university chemistry students, while data for partial least square analysis was collected from 441 Chinese pre-university chemistry students. Exploratory factor analysis (EFA) revealed that the constructed CHC Scale is four-dimensional, namely principled, dependence on teacher, harmony, and education, while the PtAL Scale is ten-dimensional, namely action, perceived values, application into life, examination, disappointed with self, uncomfortable, confidence, optimistic, embarrassment, and unbothered. Partial least square analysis (PLS-SEM) revealed that CHC has a positive effect on PtAL. This means that if the CHC students perceived the culture that they experienced (as reflected in their beliefs and attitude), outweighed the costs and problems of engaging in AL, to be rewarding, they were more inclined towards AL, and vice versa. Thus, it is vital to have a deep cultural understanding and holistic perspectives into CHC.